Energy exchanges in carbon nanotube oscillators - Zhao, Yang (2011)
Energy exchanges between orderly intertube axial motion and vibrational modes are studied for isolated systems of two coaxial carbon nanotubes at temperatures ranging from 300 to 500 K. It is found that the excess intertube